Pengaruh Pelayanan Gereja dan Perhatian Orang Tua terhadap Pembentukan Karakter Anak Sekolah Minggu di HKBP Partahanan Medan - Rocky Owen Sinambela; Hisardo Sitorus; Sudirman Lase; Albiner Siagian; Johari Manik (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The objectives of this study are 1) to determine the influence of church ministry on the character formation of Sunday School children at HKBP Partahanan Medan; 2) to determine the influence of parental attention on the character formation of Sunday School children at HKBP Partahanan Medan; and 3) to determine the combined influence of church ministry and parental attention on the character formation of Sunday School children at HKBP Partahanan Medan. This study employed a quantitative method with inferential statistics. The sample consisted of 31 Sunday School congregants. Data were collected through questionnaires and analyzed using regression and correlation tests. The results indicate that: 1) Church ministry has a positive and significant influence on the character formation of Sunday School children, with an F-value of 60.290 and a significance level of 0.000; 2) Parental attention has a positive and significant influence on the character formation of Sunday School children; and 3) Church ministry and parental attention jointly exert a positive and significant influence, contributing 71.6% to the variation in children’s character formation.Thus, it can be concluded that effective church ministry and consistent parental attention are the primary factors influencing the character formation of Sunday School children at HKBP Partahanan Medan.